2020
DOI: 10.1093/ehjci/jeaa285
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–volume loop validation of TAPSE/PASP for right ventricular arterial coupling in heart failure with pulmonary hypertension

Abstract: Aims The aim of this study was to validate the tricuspid annular plane systolic excursion/systolic pulmonary artery (PA) pressure (TAPSE/PASP) ratio with the invasive pressure–volume (PV) loop-derived end-systolic right ventricular (RV) elastance/PA elastance (Ees/Ea) ratio in patients with heart failure with reduced ejection fraction (HFREF) and secondary pulmonary hypertension (PH). Methods and results The relationship of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…The left and right heart catheter measurements were carried out as described previously 16 . The forward cardiac output was calculated using the Fick method.…”
Section: Methodsmentioning
confidence: 99%
“…The left and right heart catheter measurements were carried out as described previously 16 . The forward cardiac output was calculated using the Fick method.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring Ees/Ea in pressure-volume loops as a surrogate for RV-PA coupling is the current, invasive gold standard for the assessment of the RV function in relation to pulmonary afterload and the transition to right heart failure [ 8 ]. TAPSE/PASP correlates well with Ees/Ea in patients with HFpEF [ 16 ] and HFrEF [ 28 ]. It was also associated with higher mortality in HFpEF and in HFrEF patients [ 14 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAPSE/PASP correlates well with Ees/Ea in patients with HFpEF [ 16 ] and HFrEF [ 28 ]. It was also associated with higher mortality in HFpEF and in HFrEF patients [ 14 , 28 , 29 ]. Studies in patients with PH also showed an independent association of TAPSE/PASP with Ees/Ea, suggesting that TAPSE/PASP could be a non-invasive parameter of RV-PA coupling [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its technical complexity, the assessment of RVPAC is not routinely performed. However, non-invasive estimation of RVPAC can be done using cardiac magnetic resonance (CMR) [7] or transthoracic echocardiography [8], and non-invasive parameters showed good correlation with catheterisation-derived measurements [7][8][9][10]. Three-dimensional (3D) echocardiography overcomes the pitfalls of conventional RV functional assessment [11] and has been validated against CMR [12].…”
Section: Introductionmentioning
confidence: 99%